The troubles with postmodernism - Morawski, Stefan (Routledge, 1996)
As it nears the millennium European and American culture is dominated by that sense of something long dominant in the process of collapse which we call the condition of post-modernity. Stefan Morawski here attempts to unravel the complex strands which link our perception of postmodernism and postmodernity with aesthetic and human values whose roots lie deep in history. His discussion of modern art, film, literature and architecture ranges widely over the European tradition and offers an impassioned interrogation of the ways in which we understand, evaluate and use contemporary culture.